Florbetapir positron emission tomography and cerebrospinal fluid biomarkers. Issue 8 (24th April 2015) - Hake, Ann; Trzepacz, Paula T.; Wang, Shufang; Yu, Peng; Case, Michael; Hochstetler, Helen; Witte, Michael M.; Degenhardt, Elisabeth K.; Dean, Robert A.; ,
Abstract: Background: We evaluated the relationship between florbetapir‐F18 positron emission tomography (FBP PET) and cerebrospinal fluid (CSF) biomarkers. Methods: Alzheimer's Disease Neuroimaging Initiative‐Grand Opportunity and Alzheimer's Disease Neuroimaging Initiative 2 (GO/2) healthy control (HC), mild cognitive impairment (MCI), and Alzheimer's disease (AD) dementia subjects with clinical measures and CSF collected ±90 days of FBP PET data were analyzed using correlation and logistic regression. Results: In HC and MCI subjects, FBP PET anterior and posterior cingulate and composite standard uptake value ratios correlated with CSF amyloid beta (Aβ1–42 ) and tau/Aβ1–42 ratios. Using logistic regression, Aβ1–42, total tau (t‐tau), phosphorylated tau181P (p‐tau), and FBP PET composite each differentiated HC versus AD. Aβ1–42 and t‐tau distinguished MCI versus AD, without additional contribution by FBP PET. Total tau and p‐tau added discriminative power to FBP PET when classifying HC versus AD. Conclusion: Based on cross‐sectional diagnostic groups, both amyloid and tau measures distinguish healthy from demented subjects. Longitudinal analyses are needed.